A rapid shift in the sediment routing system of Lower-Upper Oligocene strata in the Qiongdongnnan Basin (Xisha Trough), Northwest South China Sea. (June 2019) - Lei, Chao; Clift, Peter D.; Ren, Jianye; Ogg, James; Tong, Chuanxin
Abstract: The Oligocene is a period of continental breakup in the South China Sea and of earth surface topographic change in the southeastern margin of the Tibetan Plateau. In previous studies, Oligocene sediment from the Qiongdongnan Basin (QDNB) in the NW South China Sea has seldom been recovered, which limited understanding of basin evolution at this time. Here, we apply detrital zircon U-Pb dating to Oligocene sedimentary rocks from the QDNB. The U-Pb age populations in Lower Oligocene highlight the distinctive signatures of several competing sources providing material from nearby structural highs within the basin and Hainan island. In contrast, detrital zircon U-Pb ages of the Upper Oligocene in the central QDNB shows similarities with the Red River and/or coastal rivers in northern Vietnam. These sediments are significantly different from the Lower Oligocene. This abrupt change in the QDNB may imply that its distal sedimentary sources were initially established in the Late Oligocene. Our reconstruction of sediment discharge from proximal to distal sources in the Oligocene improves understanding of the sediment distribution in the QDNB, which will implicate the river drainage evolution and benefit the petroleum exploration of the Northwest South China Sea. Highlights: U-Pb age spectra represents an abrupt change from simple pattern in the Lower Oligocene to multiple age peaks in the Upper Oligocene. Lower Oligocene sediments in the Qiongdongnan Basin were locally sourced. Late Oligocene connection between the Red River and NW South China Sea was preserved in the sediments within the Qiongdongnan Basin.